Re-Culturing Educator Preparation Programs: A Collaborative Case Study of Continuous Improvement. Issue 4 (2nd October 2017) - Snow, Jennifer; Dismuke, Sherry; Zenkert, A. J.; Loffer, Carolyn
ABSTRACT: Teacher educators at one institution of higher education collaborated to reculture systems for a focus on continuous improvement even within mounting accountability pressures. A framework of social network theory allowed for themes to develop around layered interactions of faculty, processes, and professional capital. Findings focused on people, groups, and systems for sustaining a culture of continuous improvement.